Intersectionality and social change - Woehrle, Lynne M., 1965- (Bingley, U.K. : Emerald, 2014)
Volume 37 explores the question, what can the emerging discipline of intersectionality studies contribute to our quest to understand and analyze social movements, conflict and change? This collection is part of a continued broadening and deepening of the theoretical contributions of intersectional analysis in understanding social structures and human practices. It lends analytical eye to questions of how race, class, and gender shape strategy and experience in social change processes. It also stretches to include thinking about how analysis of age, religion, or sexual identity can influence the model. The papers contribute to our growing understanding of ways to use the social power analysis unique to the intersectional lens to offer new perspectives on well-researched questions such as group identity development in conflict, coalition organizing, and movement resonance. Through the intersectional lens questions often ignored and populations traditionally marginalized become the heart of the analysis. Additionally, the volume also considers how surveillance and information sharing shape the complex relationship between democratic freedoms and hegemonic governmental systems.
Political intersectionality within the Spanish indignados social movement / Marta Cruells López, Sonia Ruiz García -- Agonism and intersectionality : indigenous women, violence and feminist collective identity / Sarah Maddison, Emma Partridge -- Mothers, Mizrahi and poor : contentious media framings of mothers' movements / Noa Milman -- Age dynamics and identity : conflict and cooperation among feminists in Buenos Aires / Elizabeth Borland -- From intragroup conflict to intergroup cooperation / Jay Rothman -- Social movements and bridge building : religious and sexual identity conflicts / Jonathan S. Coley -- Shadows of solidarity : identity, intersectionality and frame resonance / Amaka Okechukwu -- AIDS activism among African American women : identity and social justice / Angelique C. Harris -- The dynamics of backlash online : anonymous and the battle for WikiLeaks / Jennifer Earl, Jessica L. Beyer -- What makes protest dangerous? Ideology, contentious tactics, and covert surveillance / Patrick Rafail.
Print version record
Keywords: Political Science -- Peace; Political Science -- Political Freedom & Security -- General; Political activism; Political control & freedoms; Demonstrations & protest movements; Deliberative democracy; Social change; Social movements; Group identity